IMPACT OF CHLORIDE ION CHANNEL CLC4 ON BLADDER CANCER PROGRESSION (Journal of Medical & Health Sciences Review, 2025)
Oncogene and tumour suppressor gene mutations cause heterogeneous cancer. About 10 million people die due to cancer annually. Bladder cancer is one of the most common cancers worldwide, predominantly in men. It is reported that ion channels are involved in cell proliferation, differentiation, apoptosis, tumour cell motility, invasion, and metastasis; hence, cancers are channelopathies. This study examined the expression of chloride ion channel CLC4 in bladder cancer. We collected 20 pairs of tumours and normal tissue samples from bladder cancer patients for the expression analysis. We observed an increase in CLC4 mRNA expression. Mutations in CLC4 gene cause chloride ion channel changes that promote cancer. Understanding chloride channel molecular mechanisms require more research.